Analysing head and trunk motion in the judo osoto-gari technique: relationship to sweeping-leg velocity - Lingjun Liu; Tatsuya Deguchi; Mitsuhisa Shiokawa; Kazuto Hamaguchi; Masahiro Shinya (PeerJ)
Background Osoto-gari is a leg throw technique that primarily relies on the hip extension to initiate the sweeping motion of the leg. A high sweep contact velocity is a crucial factor in efficiently executing this technique. While some literature emphasises whole-body coordination in the leg-sweeping action, the roles of trunk and head motion remain unclear. This study investigates head and trunk movements (including the pelvic and upper torso) contributing to higher leg-sweep velocities when executing the judo osoto-gari. Methods Kinematic data were collected from 17 male black-belt judokas using a motion capture system (250 Hz). Pearson product-moment correlation and stepwise linear regression were used to identify kinematic variables linked to the sweeping-leg velocity at sweep contact (SC). Results Six out of twenty-four variables correlated with sweeping-leg velocity at SC. A stepwise regression model (adjusted R2 = 0.53, p = 0.009) predicted sweeping-leg velocity based on head-tilt angle at maximum sweeping-leg height (MSH) and SC, head-tilt angular velocity at MSH, and trunk-tilt angular velocity at MSH. Conclusions The findings of this study indicate that (1) increasing the forward angle of the head aids the visual system in rapidly processing spatial information about the target position, thus facilitating the execution of the leg sweep, and (2) a greater forward-tilt rotation of the head, which leads to rapid trunk rotation, is conducive to enhancing sweeping-leg velocity.